2001
DOI: 10.1021/es0107475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polybrominated Diphenyl Ethers and Their Capacity to Induce CYP1A by the Ah Receptor Mediated Pathway

Abstract: Polybrominated diphenyl ethers (PBDEs) have become widely distributed as environmental contaminants due to their use as flame retardants. Their structural similarity to other halogenated aromatic pollutants has led to speculation that they might share toxicological properties such as hepatic enzyme induction. In this work we synthesized a number of PBDE congeners, studied their affinity for rat hepatic Ah receptor through competitive binding assays, and determined their ability to induce hepatic cytochrome P-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
96
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(106 citation statements)
references
References 41 publications
8
96
1
1
Order By: Relevance
“…There was no EROD induction by DE71 in both cultured gill epithelia and hepatocytes in the present study, although a weak EROD induction was reported in BDE-77, 100, 153, and 183 in mammalian cell lines (Chen et al, 2001;Behnisch et al, 2003) and in primary cultured rat hepatocytes (Rattus norvegicus) (Chen et al, 2001;Chen and Bunce, 2003). Our results are consistent with previous experiments in primary cultured carp (Cyprinus carpio) hepatocytes (Kuiper et al, 2004) and monkey (Macaca fascicularis) hepatocytes (Peters et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…There was no EROD induction by DE71 in both cultured gill epithelia and hepatocytes in the present study, although a weak EROD induction was reported in BDE-77, 100, 153, and 183 in mammalian cell lines (Chen et al, 2001;Behnisch et al, 2003) and in primary cultured rat hepatocytes (Rattus norvegicus) (Chen et al, 2001;Chen and Bunce, 2003). Our results are consistent with previous experiments in primary cultured carp (Cyprinus carpio) hepatocytes (Kuiper et al, 2004) and monkey (Macaca fascicularis) hepatocytes (Peters et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Szabo et al (2009) indicated that UGT-T4 is not the most sensitive marker for DE-71, and the regulation of UGT to THs is thought to be nuclear receptor specific. Since BDE-209 has a very limited potential to activate the transcriptional factor, aryl hydrocarbon receptor (AhR) (Chen et al, 2001;Villeneuve et al, 2002), the decreased T4 levels in our study may not be directly related to the regulation of UGT. Therefore, the mechanistic relationships between metabolic genes and THs upon BDE-209 exposure require further study.…”
Section: Discussionmentioning
confidence: 80%
“…Polychlorinated biphenyl (PCBs) and polybrominated diphenyl ethers (PBDEs) have been manufactured in large quantities and are contained in many industrial and consumer products [1,2]. It was reported that both PCBs and PBDEs possess dioxin-like activity, and all of them are toxic, endocrine disrupting, and probably carcinogenic [3,4]. Because all these three groups of pollutants are ubiquitous, it is likely that they co-exist in most environmental matrices [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%